Usulan Perbaikan Tata Letak Fasilitas Terhadap Optimalisasi Jarak dan Ongkos Material Handling Dengan Pendekatan Systematic layout planning (SLP) di PT Transplant Indonesia - Muslim, Dede; Ilmaniati, Anita (Jurnal Media Teknik dan Sistem Industri, 2018)
Abstract – Unplanned layout and inefficient material flow between work units can lead to increased cost. PT Transplan Indonesia's current material flow path is inefficient with material flow distance 115.5 meters and material handling cost that has not been taken into account. This study aims to find out how big the role of facility layout design in cutting the distance of material transfer and pressing the cost of material handling. The method used in this research is Systematic Layout Planning (SLP) approach, which is comparing the distance of material transfer between initial layout with proposed layout. The results of this study indicate that the distance of the material flow path on the production floor with proposed layout changed to 71,7 meters, with material handling cost per meter reduced from Rp. 1,105,954 to Rp. 712,402 or decrease as much as 35%. Based on the results of the research, the layout of the proposal is considered more effective and efficient because it can reduce the distance of material transfer and reduce the cost of material handling on the packing/shipping floor.Keywords: Layout Design; Material handling cost; Systematic Layout Planning (SLP)